DHABĪḤULLĀH DAN POLITIK IDENTITAS MUSLIM AWAL: Kajian Kritis Atas Tafsīr Al-Kabīr Muqātil Bin Sulaimān - Mohammad -Husen; Dluha Luthfillah (Institut Agama Islam Negeri (IAIN) Keiri, 2019)
This article talked about the differing opinions of commentators on dhabīḥullāh by giving more focus to Muqātil bin Sulaymān (d. 150/767). Unlike the general commentators who understood that Ishmael was slaughtered by Ibrahim, Muqātil mentioned the name Ishaq. This name is also mentioned by prominent commentators and historians, al-Ṭabarī, and also by the Old Testament. In addition to considering the narratives mentioned in other parts of the Qur’an, the basis of the opinion of this faction is the various narrations whose numbers actually compete with the narrations of Ishmael as dhabīḥullāh. However, what is interesting is the relationship between these two interpretations with the identity politics of the early Muslim community. By using the documentation method, the writer lists interpretations that appear in several books which for some reasons. The author considered to have represented each century. With this the author discovers a unique distribution of the opinions of dhabīḥ-Ismail. He appeared as an alternative in the early commentaries, and then it became the main narrative in the books that appeared after ibn Kathīr. The loss of this opinion in the commentary books turns out to coincide with the process of the formation of Islamic orthodoxy which could be only a consequence of certain hermeneutic principles or part of the differentiation agenda. This last alternative, if confirmed, can be considered to agree with the opinion of Western scholars about the gradualist of Islamic orthodoxy and furthermore the identity of Islam as a religion.